Introduction to geomedia histories. (November 2022) - Fast, Karin; Abend, Pablo
The maturation of mobile, convergent, and place-contingent technologies has inspired researchers from different fields to re-imagine the relationship between geography and media. Recently, the linking of site-specific media and mediatized places culminated in the overarching concept that sits at the midpoint of this special issue: geomedia. While the majority of work within geomedia studies focuses on contemporary developments, thereby offering snapshots of geomediatization processes as these currently manifest themselves, this volume wants to address the nexus of geography and media from a decidedly historical perspective. Doing so, we hope to inspire a historical turn in geomedia studies as well as contribute to the ongoing discussion about how to define geomedia (studies) beyond (the study of) particular technologies or media genres. By boldly uprooting the geomedia concept from its contemporary, predominantly digital, framework, the contributions gathered here encourage us to map the trajectories of geomedia, to challenge "geomediatization realism, " to remedy epistemological biases, and to further articulate the postdigital.